Attachment security and violence: the role of reflective functioning capacity$dthe role of reflective functioning capacity - Kiessling-Caver, Anita (Criminology, criminal justice, law & society, 2018)
The quality of attachment security and the ability to effectively relate to another person’s distress has been understood as a linkage that can often alert researchers and practitioners to potential problematic behaviors in children, including violence, which can often become more pervasive and severe in adulthood. This qualitative study examined the role of reflective functioning capacity in adults with a history of extremely violent behaviors. Seventeen adults participated in the study and were administered the Adult Attachment Scale (AAS) to determine attachment classification. They also participated in semi-structured interviews regarding the quality and perception of their childhood environments. As a component of the grounded theory methodology, negative case analysis was utilized to ensure presentation of deviant cases that would challenge emerging ideas or patterns. As such, the participants had both violent and non-violent criminal histories as well as both insecure and secure attachment classifications. Findings indicated two primary categories potentially affecting future violence: responsiveness of environment and distortions in the internal working model. During qualitative analysis, the capacity to mentalize, as a component of the internal working model, was found to be an important variable in determining violent behaviors in both secure and insecurely attached participants